Organizational structures, gender roles and upgrading strategies for smallholders in developing countries' local value chains - Ayobami Adetoyinbo; Verena Otter (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2020)
To achieve the Sustainable Development Goals, research concepts and empirical evidence are needed to upgrade developing countries' smallholder activities within local value chains (LVCs). The study aims to uncover LVCs' (1) organization, (2) governance themes and gender roles for value addition and (3) smallholder upgrading strategies in developing countries' dualistic sectors. The global value chain (GVC) framework is extended towards a gendered value web approach that captures the importance of hidden gender roles and power relations. Empirical data obtained from 3 focus group discussions and 21 interviews in the Nigerian shrimp and prawn sector represent the basis for qualitative analysis. The results indicate that, despite being driven by competitive traders, mutually reliant coordination between production and processing segments and strategic business activities of female processors are crucial for the LVCs' functioning. Based on these results, manifold managerial and policy implications which can also apply to other developing countries and cases are derived to upgrade and develop smallholder activities and products along the Nigerian shrimp and prawn LVC.
Keywords: L2; Q13; D46; Q22; J16; 330; Governance themes; Gender; Global value chain framework; Value web approach; Smallholder upgrading strategies; Nigerian shrimp and prawn